2020
DOI: 10.3390/universe6010019
|View full text |Cite
|
Sign up to set email alerts
|

Editorial for the Special Issue “Progress in Group Field Theory and Related Quantum Gravity Formalisms”

Abstract: This Editorial introduces the Special Issue "Progress in Group Field Theory and Related Quantum Gravity Formalisms" which includes a number of research and review articles covering results in the group field theory (GFT) formalism for quantum gravity and in various neighbouring areas of quantum gravity research. We give a brief overview of the basic ideas of the GFT formalism, list some of its connections to other fields, and then summarise all contributions to the Special Issue.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For a triangulation with N building blocks, the resulting action (75) describes a theory of N coupled particles that carve out a trajectory on the superspace of discrete and selfdual geometries on the lattice. Strikingly similar ideas can be found in group field theory (GFT), which is an approach to quantum gravity where the kinematical wave function for an individual building block is promoted into a second-quantized field operator [47][48][49][50]. In this way, transition amplitudes for simplicial boundary states turn into Feynman amplitudes for an auxiliary quantum field theory on the underlying configuration space, which is a sortof mini-superspace of geometry (in three spatial dimensions, this is usually G 4 /G for gauge groups G = SU (2) or G = SL(2, C)).…”
Section: Outlook and Discussionmentioning
confidence: 70%
“…For a triangulation with N building blocks, the resulting action (75) describes a theory of N coupled particles that carve out a trajectory on the superspace of discrete and selfdual geometries on the lattice. Strikingly similar ideas can be found in group field theory (GFT), which is an approach to quantum gravity where the kinematical wave function for an individual building block is promoted into a second-quantized field operator [47][48][49][50]. In this way, transition amplitudes for simplicial boundary states turn into Feynman amplitudes for an auxiliary quantum field theory on the underlying configuration space, which is a sortof mini-superspace of geometry (in three spatial dimensions, this is usually G 4 /G for gauge groups G = SU (2) or G = SL(2, C)).…”
Section: Outlook and Discussionmentioning
confidence: 70%
“…These equations have to be satisfied for every operator Ô in the GFT Hilbert space. In particular, notice that a state satisfying (10) automatically satisfies the Schwinger-Dyson equation for Ô = . In this sense both choices are approximately equivalent.…”
Section: Gft Dynamicsmentioning
confidence: 99%
“…[34]. There, it was shown that one can derive an equation like (10) by starting with the Hamiltonian constraint of LQG and translating it into a constraint in the Hilbert space of GFT, which can be done given the relation between the Hilbert spaces of both approaches that I have highlighted above. In this sense, one can try to justify the adoption of canonical GFT by appealing to LQG.…”
Section: Gft Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once we have chosen basic variables, here the spinors, it is natural to proceed to a Taylor expansion of the functionals and thus consider polynomial ansatz (of increasing power) for the Hamiltonian H[{z k }]. If the quadratic ansatz, corrected by potential higher order terms, does not yield expected or realistic physics, then this usually indicates that we have made the wrong choice of basic variables and that we should very likely consider a different phase for spin networks (for example, consider a type of condensate of spin networks, as proposed in the group field theory approach [49][50][51]) and the corresponding different boundary data for loop quantum gravity on space-time corners.…”
Section: Spinor Dynamics On the 2 + 1-dimensional Time-like Boundarymentioning
confidence: 99%